make one equation = 0
so 2(0)-3y=6
3y/3=6/3
y=2
now
2x-3(2)=6
2x-6=6
2x=6+6
2x=12
2x/2=12/2
x=6
now sub that it to the other side
y=4(6)-7
y=24-7
y=17
2=4x-7
2+7=4x
9=4x
9/4=4x/4
2.25=x
Solve by substitution..
y=4x-7 and 2x-3y=6
This is the only question i am stuck on, please help..
2 answers
Since it says Solve by substitution..
y=4x-7
2x-3y=6
just substitute in 4x-7 for y in the 2nd equation:
2x-3(4x-7) = 6
2x-12x+21 = 6
-10x = -15
x = 3/2
y = 4x-7 = 4(3/2)-7 = 6-7 = -1
Paul's solution method is strange (and wrong). Using the intercepts will not help in finding the intersection.
y=4x-7
2x-3y=6
just substitute in 4x-7 for y in the 2nd equation:
2x-3(4x-7) = 6
2x-12x+21 = 6
-10x = -15
x = 3/2
y = 4x-7 = 4(3/2)-7 = 6-7 = -1
Paul's solution method is strange (and wrong). Using the intercepts will not help in finding the intersection.